Failure characteristic and fracture evolution law of overburden of thick coal in fully mechanized sub-level caving mining - Wang, Xiaolei; Qin, Qirong; Fan, Cunhui (Penerbit Universiti Kebangsaan Malaysia, 2017)
In mining process, the height of water flowing fractured zone is important significance to prevent mine of water and gas, in order to further research the failure characteristic of the overlying strata. Taking certain coal mine with 5.82 m mining height as the experimental face, by using the equipment which is sealed two ends by capsules in borehole, affused measurable water between the two capsules and borehole televiewer system, ground penetrating radar, microseismic monitoring system in underground coal mine, the height of water flowing fractured zone of fully-mechanized top caving are monitored, a numerical simulation experiment on the failure process was conducted, a similarity simulation experiment on the cracks evolution was conducted, at the same time, empirical formula of traditional was modified, The results showed that the height of caving and fractured zones were respectively 43.1 and 86.7 m in fully mechanized sub-level caving mining. The data difference of each test method of caving, fractured and water flowing fractured zones were respectively less than 4.5%, 7.1% and 9.0%. The degree of fracture development was low before mining, the number of fissures was obviously increased after mining, the degree of fracture development increased. The fractures cluster region mainly focuses near the coal wall. The fractures density distribution curves of overlying strata like sanke-shapes. The new and adapt to certain coal mine geological conditions empirical formula of water flowing fractured zone height is proposed.